Experimental investigation of shape-enhanced rotating cylinders with electric heaters and solar panels for augmented pyramid solar still performance - A. S. Abdullah; Mutabe Aljaghtham; Wissam H. Alawee; Z. M. Omara; Fadl A. Essa (PLoS ONE, 2026)
This work investigated the influence of various amendments on a pyramid solar still with rotating cylinders (RCPSS) and rotating corrugated cylinders (RCCPSS). We compared distillate yield from the RCPSS with a baseline design (PSS) to assess the effectiveness of each modification. The study explored incorporating reflectors, silver nanoparticle-infused phase change material (PCM-Ag) composites within the cylinders, and a vapor-withdrawing fan with an external condenser. In addition, three electric heaters were fixed on the basin water to raise its temperature. The energy required to run the heaters was captured from a PV system. Also, the effect of covering corrugated cylinders with wick on the performance of the modified still was also studied. The RCCPSS significantly outperformed the PSS, producing 8500 mL/m² of freshwater daily compared to 3100 mL/m², representing a 174% increase in distillate. Additionally, heaters and PCM-Ag composites further enhanced distillate yield by 244% and 365%, respectively. However, the most optimal configuration involved combining a wick, heaters and fan. This setup yielded the highest distillate production (14950 mL/m²), a 382% increase over PSS, and achieved a thermal efficiency of 75%. Finally, the freshwater production cost was lower for the RCPSS with wick, heaters and fan ($0.01/L) compared to the PSS ($0.02/L). The work demonstrates a strong commitment to advancing the United Nations Sustainable Development Goals (SDGs), particularly SDG 6: Clean Water and Sanitation.